Improving Customer Value Through the Integral of Techniques Quality Function Deployment and Value Engineering - Mohammed A. Al-Adhami, Zaid; Abdul Kareem H. Alrawi, Maha (Journal of Economics and Administrative Sciences, 2022)
Health service institutions suffer from challenges resulting from the great changes that our world is witnessing today. This has affected the value that these institutions add to the patient. This research aims to identify the effect of integrating each of the techniques of QFD and value engineering for the health services provided to the patient to improve the value for him and thus obtain his satisfaction, which is reflected in the reputation of the surveyed hospitals. To achieve this, the descriptive analytical method was used, and a questionnaire was designed to collect the necessary data, which represents a measure of this research. The questionnaire was distributed to a sample deliberately taken from the research community consisting of hospital directors, department managers, and divisions in research hospitals, where the sample size was (97) individuals. Various statistical methods were used to test the research hypotheses, including confirmatory factor analysis and path analysis. The results were extracted using SPSS and Amos. The quality function diffusion and value engineering had an effective and substantial effect in improving value for patients in the surveyed hospitals, which is the most important finding of this research. One of the most important recommendations of the research is to work on the participation of health staff in the health sector with the academic authorities represented by universities and specialized colleges and to work on continuing consultations to implement methods that contribute to achieving the highest levels of quality of health services. Paper type: Research paper.